Dysfluencies in Normals under DAF : in Three Conditions of Voicing - Nataraja NP; Venkatesh CS; Kushal Raj P (Journal of All India Institute of Speech and Hearing, 1970)
Several studies have reported that the normals show stuttering like behaviour under DAF. There are also studies showing that the stutterers show different degrees of adaptation under different degrees of voicing. The present study was conducted to find out the adaptation in 15 male and 15 female normal adults  under DAF in 3 different voicing conditions (silent, whisper and loud reading). The results indicate greater adaptation in  these  subjects  under  silent  reading  compared  to other conditions.